(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
Microbial contamination in food can pose a serious threat, as it not only reduces food quality but also directly impacts health, ranging from mild to severe conditions, and can affect people of all ages. Adolescents are vulnerable to food poisoning due to limited knowledge and skills in safe food handling. This community service activity involved partners from SMAN 6 Depok and aimed to address the main problems faced by teenagers, such as limited knowledge about the types of microorganisms that can cause contamination in food. Educating adolescents is crucial, considering that the highest cases of food poisoning occur in this age group, yet education efforts are still rare because most health programs focus on groups directly involved in food processing. The methods used include interactive educational approaches, such as presentations, discussions, and Q&A sessions, as well as laboratory practices to observe microorganisms with the aid of a microscope. The activity also involved administering questionnaires in the form of pre-tests and post-tests to the adolescents. The results of the activity showed a significant increase in knowledge about the types of microorganisms that cause food contamination, from 40% to 96%. This educational program has strong sustainability potential with long-term impacts in the form of increased adolescents’ knowledge and a reduced risk of foodborne diseases.